Að Jökla: Ecolinguistic Activism through Acoustic Ecology, Countermapping, Travel Wreading, and Conversations with Landscapes - Rawlings, Angela Marie 1978- (2014)
This thesis explores the potential for ecolinguistic activism to act as a gateway for experiential learning via the generation of site-dependent artwork related to place—specifically, glaciers in Iceland. Through the exploration of non-conventional pedagogy within an artist’s context, the relationship between humans and glaciers unfolds in multidisciplinary art documenting long-term engagement with soundscapes, countermapping, travel wreading, and conversations with landscapes. Acoustic ecology provides sound education exercises through ear cleaning, soundwalks, and vocal improvisation, resulting in the participant’s increased awareness of listening as both sensorial practice and as comprehension. Countermapping and travel wreading offer non-conventional modes of dwelling within language and literature. Attempted conversations with landscapes situate the participant within a theatre of the rural, in which reciprocal perception shifts the relatability of linguistic category, emotional connection, and utility. The thesis’ main conclusion is that autoethnographic methodology demonstrates the effectiveness of pedagogy focused on transformative action, and documentation of art-making processes offers repeatable models that may result in action competence with the power to alter a person’s notion of herself as a place-maker and of her interconnectedness with ecosystems in flux. Keywords: Ecolinguistics, countermapping, acoustic ecology, sustainability pedagogy